Asylum Company records - Asylum Company
Minutes (1794 April 23-1797 June 7) of the Asylum Company relating to land speculation in northeastern Pennsylvania; and letter (1814 August 10) of Matthias Hollenback, land agent.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Land company located in Philadelphia, Pa.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hollenback, Matthias, -- 1752-1829.; Land companies -- Pennsylvania -- Philadelphia; Land speculation -- Pennsylvania